Percutaneous calcium phosphate cement injection for unicameral bone cysts: mid- to long-term clinical and radiographic outcomes - Mengzhang Xie; Zhengxiao Lai; Yi Luo; Li Min; Chongqi Tu; Yong Zhou (Frontiers in Surgery, 2026)
Objective Unicameral bone cysts (UBCs) are fluid-filled, osteolytic lesions commonly affecting children and adolescents. Minimally invasive treatments such as percutaneous injection have become increasingly popular. Calcium phosphate cement (CPC), a biocompatible artificial bone substitute with mechanical strength and osteoconductivity, and may be suitable for such applications. This study aimed to evaluate the mid- to long-term clinical and radiographic outcomes of percutaneous calcium phosphate cement injection for UBCs, with particular emphasis on late recurrence, repeat injection, cortical remodeling, and cavity filling. Methods A retrospective review was conducted on 31 patients with UBC treated by CPC injection between January 2013 and January 2025, with at least 1 year of follow-up. Postoperative outcomes were assessed radiographically, functionally, and for complications. We recorded the patients’ age, sex, preoperative and postoperative visual analog scale (VAS) scores, Musculoskeletal Tumor Society (MSTS) scores, modified Neer classification and Capanna classification, cortical thickness ratio, cavity filling, recurrence, repeat intervention, and complications. Results The mean follow-up duration was 61.1 months (range, 13–149 months). Among them, 14 patients experienced pathological fractures. Postoperatively, pain and functional outcomes improved significantly, with the median VAS score decreasing to 0 and the median MSTS score improving to 30 at final follow-up ( P < 0.001). Recurrence after the first injection occurred in four patients (12.9%). Among them, three patients underwent repeat percutaneous CPC injection, and one patient was managed with observation because of adequate cortical thickness and clinical stability. At final follow-up after all treatments, all patients achieved modified Neer grade I or II outcomes, and most patients achieved Capanna grade I or II healing. One patient experienced delayed wound healing, and no severe complications were observed. Conclusion Percutaneous CPC injection was associated with pain relief, functional improvement, and radiographic stabilization in patients with UBCs. Repeat CPC injection appeared to provide stable outcomes in recurrent cases, whereas observation was considered reasonable for one clinically stable lesion with adequate cortical thickness. The observed cortical remodeling and cavity filling suggest that CPC injection may represent a potential minimally invasive strategy for reconstruction of UBC-related bone defects.